Age-related variations in Takotsubo syndrome - Cammann, Victoria Lucia; Szawan, Konrad A.; Stähli, Barbara Elisabeth; Kato, Ken; Budnik, Monika; Wischnewsky, Manfred Bernd; Dreiding, Sara; Levinson, Rena A.; Di Vece, Davide; Gili, Sebastiano; Citro, Rodolfo; Bossone, Eduardo; et al. (Journal of the American College of Cardiology, 2020)
Background - Takotsubo syndrome (TTS) occurs predominantly in post-menopausal women but is also found in younger patients. - Objectives - This study aimed to investigate age-related differences in TTS. - Methods - Patients diagnosed with TTS and enrolled in the International Takotsubo Registry between January 2011 and February 2017 were included in this analysis and were stratified by age (younger: ≤50 years, middle-age: 51 to 74 years, elderly: ≥75 years). Baseline characteristics, hospital course, as well as short- and long-term mortality were compared among groups. - Results - Of 2,098 TTS patients, 242 (11.5%) patients were ≤50 years of age, 1,194 (56.9%) were 51 to 74 years of age, and 662 (31.6%) were ≥75 years of age. Younger patients were more often men (12.4% vs. 10.9% vs. 6.3%; p = 0.002) and had an increased prevalence of acute neurological (16.3% vs. 8.4% vs. 8.8%; p = 0.001) or psychiatric disorders (14.1% vs. 10.3% vs. 5.6%; p < 0.001) compared with middle-aged and elderly TTS patients. Furthermore, younger patients had more often cardiogenic shock (15.3% vs. 9.1% vs. 8.1%; p = 0.004) and had a numerically higher in-hospital mortality (6.6% vs. 3.6% vs. 5.1%; p = 0.07). At multivariable analysis, younger (odds ratio: 1.60; 95% confidence interval: 0.86 to 3.01; p = 0.14) and older age (odds ratio: 1.09; 95% confidence interval: 0.66 to 1.80; p = 0.75) were not independently associated with in-hospital mortality using the middle-aged group as a reference. There were no differences in 60-day mortality rates among groups. - Conclusions - A substantial proportion of TTS patients are younger than 50 years of age. TTS is associated with severe complications requiring intensive care, particularly in younger patients.
Gesehen am 08.07.2020